CCNA Routing and Switching 200-125 - Wallace, Kevin, 1965- (LiveLessons (Indianapolis, Ind.), 2016)
CCNA Routing and Switching 200-125 Complete Video Course is a comprehensive training course that brings Cisco CCNA exam topics to life through the use of real-world demonstrations, animations, live instruction, and configurations, making learning these foundational networking topics easy and fun. Best-selling author, expert instructor, and double CCIE Kevin Wallace walks you through the full range of topics on the CCNA Routing and Switching 200-125 exam, including fundamentals of networking, LAN switching, IP routing, Wide Area Networks (WANs), network services, securing network devices, and network management. This unique product contains multiple types of video presentations, including live instructor whiteboarding, real-world demonstrations, animations of network activity, dynamic KeyNote presentations, doodle videos, and hands-on router and switch CLI configuration and troubleshooting in real lab environments, enabling you to learn both the concepts and the hands-on application. The 300+ videos contained in this product provide more than 25 hours of instruction. Modules are divided into easy-to-digest lessons and sublessons, and each lesson concludes with an interactive quiz to help assess your knowledge. The eight modules map to the exam objectives and conclude with summaries and module and glossary review quizzes, challenging you to recall information across multiple topics. Forty-six interactive hands-on exercises are integrated throughout the course, challenging you to apply the knowledge you’ve learned in each lesson. The product concludes with a series of lessons that give you valuable advice to help prepare for the actual exam. Designed to take you inside CCNA networking concepts in a unique and interactive way, CCNA Routing and Switching 200-125 Complete Video Course is guaranteed to help you master the foundational networking topics that will help you succeed on the exam and on the job.